2023
DOI: 10.1038/s41380-023-01981-9
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear receptor 5A2 regulation of Agrp underlies olanzapine-induced hyperphagia

Abstract: Antipsychotic (AP) drugs are efficacious treatments for various psychiatric disorders, but excessive weight gain and subsequent development of metabolic disease remain serious side effects of their use. Increased food intake leads to AP-induced weight gain, but the underlying molecular mechanisms remain unknown. In previous studies, we identified the neuropeptide Agrp and the transcription factor nuclear receptor subfamily 5 group A member 2 (Nr5a2) as significantly upregulated genes in the hypothalamus follow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…Additionally, mice exhibited no preference between the two diets ( Figure S1A ), suggesting that the added clozapine did not significantly change the taste of the control diet. Previous studies have shown that the metabolic effects of APDs are substantially more potent in female mice 19,22,26 . Thus, we measured the chronic and acute effects of clozapine on energy metabolism in female C57BL/6 mice.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Additionally, mice exhibited no preference between the two diets ( Figure S1A ), suggesting that the added clozapine did not significantly change the taste of the control diet. Previous studies have shown that the metabolic effects of APDs are substantially more potent in female mice 19,22,26 . Thus, we measured the chronic and acute effects of clozapine on energy metabolism in female C57BL/6 mice.…”
Section: Resultsmentioning
confidence: 97%
“…Given their unique binding profiles, individual APDs likely engage distinct brain circuits to alter energy metabolism. However, emerging evidence suggests that some commonly used APDs may converge on central melanocortin neurons to induce hyperphagia and weight gain 19,22 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations